Clearing Traffic Jams During Protein Translocation Across Membranes - Wang, Lihui; Ye, Yihong (Frontiers in Cell and Developmental Biology, 2021)
Protein translocation across membranes is a critical facet of protein biogenesis in compartmentalized cells as proteins synthesized in the cytoplasm often need to traverse across lipid bilayers via proteinaceous channels to reach their final destinations. It is well established that protein biogenesis is tightly linked to various protein quality control processes, which monitor errors in protein folding, modification and localization. However, little is known about how cells cope with translocation defective polypeptides that clog translocation channels (translocons) during protein translocation. This review summarizes recent studies, which collectively revealed a set of translocon-associated quality control (TAQC) strategies for eliminating polypeptides stuck in protein-conducting channels in the endoplasmic reticulum (ER) and mitochondria.